Indianista, lesbiana y sin hijos - Verushka Alvizuri (Mélanges de la Casa de Velázquez)
This article connects a fictional character with the normative discourses that weigh on «indigenous women» in contemporary Bolivian society. Saturnina Mamani, the fictional character, is both Indianist and feminist, two commitments incompatible due to the masculine character of Indianism and to the mistrust with which women from the most vulnerable sectors perceive feminism. The novel depicts the political fiction of a decolonized Bolivia, where the oppression of the Indians has ended, but where women are still oppressed. This leads the protagonist towards a separatist feminism that stands as a form of struggle against a patriarchal society. The use of fiction deserves to be questioned, taking into account the context of publication and the policy of decolonization carried out by the governments of Evo Morales.